NPS, New Production System : - Shinohara, Isao (Productivity Press, 1988)
This is a translated book from Japanese. It is valuable for the ideas imparted, but is not particularly easy to read or easy to understand. The focus is on true JIT. Make only what is ordered. Make to order. Improve systems so that manufacturing cycle is shorter than the order cycle.